DIFFERENT OF HEMATOCRIT VALUE MICROHEMATOCRIT METHODS AND AUTOMATIC METHODS IN DENGUE HEMORRHAGIC PATIENTS WITH HEMOCONCENTRATION - Meilanie, Alvin Dwi Rizky (Journal of Vocational Health Studies, 2019)
Background: Many people in Indonesia. Hematocrit examination is one of the important examinations to help diagnose dengue fever. Increased hematocrit (hemoconcentration) occurs with dengue hemorrhagic fever caused by plasma leakage. Hematocrit examination can be done by microhematocrit method and automatic method. The microhematocrit method has the principle that the blood with anticoagulants is centrifuged at a certain speed, the erythrocytes will separate from the plasma. While the automated hematology analyzer uses the principle of flowcytometry which detects based on the height of the erythrocyte pulse. Purpose: To know the differences in hematocrit values of the microhematocrit method and the automatic method in patients with hemoconcentration of Dengue Hemorrhagic Fever. Method: The study was conducted by observational analytics in March 2019 with a total of 30 samples at RSU. Haji Surabaya. The data obtained was analyzed using the Paired Sample T-Test with the SPSS 16.0 program to determine whether there were significant differences in hematocrit values between the microhematocrit method and the automatic method. Result: The results showed that the hematocrit examination results of microhematocrit method obtained an average of 46.93%, while the automatic method obtained an average of 45%. This shows the hematocrit examination results of the microhematocrit method are higher than the automatic method. Based the results of paired sample statistical tests t Tests obtained a significance value of 0.00 were less than 0.05. Conclusion: There are significant differences between the hematocrit examination results of the microhematocrit method and the automatic method.